Sierra Leone : Poverty Reduction Strategy Paper Annual Progress Report; Joint Staff Advisory Note. (IMF Staff Country Reports; Country Report ;, 2007)
This Joint Staff Advisory Note (JSAN) reviews the annual progress report (APR) for Sierra Leone Poverty Reduction Strategy Paper (SL-PRSP). The APR highlights the improvement of the economic situation in 2005 and the first half of 2006. It analyzes the key elements of the SL-PRS, including macroeconomic performance; good governance, peace, and security; pro-poor sustainable growth for food security and job creation; and human resource development. The APR highlights that the economic growth remained strong in 2005 and continued to be robust in 2006, reflecting buoyant activities in the agriculture, mining, construction, and service sectors.